2019
DOI: 10.1093/femsle/fnz062
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological linkage of vancomycin-resistant Enterococcus faecium from different sources in Ahwaz, Iran

Abstract: This study was set to determine the genetic linkage and the clonal relationship between vancomycin-resistant Enterococcusfaecium (VREfm) isolates in three hospitals of Ahwaz city. In this study, 1050 samples were collected from various rectal swabs, hands of health care workers, environmental surfaces, medical equipment and 146 enterococci isolates from clinical sources of three hospitals from March to September 2015. Antimicrobial resistance patterns in VREfm were detected by disk diffusion method. Genetic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
4
4
0
Order By: Relevance
“…In the current study, 84% of the isolates were resistant to ampicillin. This resistance rate was in agreement with the reports published by Jia et al [11], Arshadi et al [23], and Boccella et al [29] in China, Iran, and Italy, respectively, but higher than those reported by Karna et al [26] in India and Asadollahi et al [31] in Iran. The frequency of resistance to tetracycline, minocycline, and teicoplanin was 78.4%, 78.4%, and 56.8%, which was relatively similar to those reported by Asadollahi et al [31] and Arabestani et al [33] in Iran, but higher than those reported by Jia et al [11] in China, Boccella et al [29] in Italy, and Karna et al [26] inIndia and lower than the results obtained by other researchers from Egypt, India, and Iran [23,26,30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, 84% of the isolates were resistant to ampicillin. This resistance rate was in agreement with the reports published by Jia et al [11], Arshadi et al [23], and Boccella et al [29] in China, Iran, and Italy, respectively, but higher than those reported by Karna et al [26] in India and Asadollahi et al [31] in Iran. The frequency of resistance to tetracycline, minocycline, and teicoplanin was 78.4%, 78.4%, and 56.8%, which was relatively similar to those reported by Asadollahi et al [31] and Arabestani et al [33] in Iran, but higher than those reported by Jia et al [11] in China, Boccella et al [29] in Italy, and Karna et al [26] inIndia and lower than the results obtained by other researchers from Egypt, India, and Iran [23,26,30].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found a high prevalence of resistance to ciprofloxacin and levofloxacin in E. faecium isolates. This resistance rate was in agreement with the reports published by Arshadi et al [23], Sattari-Maraji et al [24], and Jia et al [22], in Iran and China, but higher than those reported by Kateete et al [25], Karna et al [26], Tian et al [27], and Arbabi et al [28] in Uganda, India, China, and Iran, respectively. Extensive or irrational use of these antibiotics to treat a wide range of bacterial infections may explain the higher resistance to this antibiotic compared to other antimicrobials.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, some studies report that most E. faecium strains isolated from intra-hospital infection cases carry three virulence factors: enterococcal surface protein ( esp ), hyaluronidase ( hyl ) and collagen-binding adhesin ( acm ) [83]. From these, only the gene acm was identified in our isolate.…”
Section: Resultsmentioning
confidence: 88%
“…The simple presence of some players may be due to their contribution to the enterococci commensal lifestyle and their noninfectious interaction with the host [ 82 ]. On the other hand, some studies report that most E. faecium strains isolated from intra-hospital infection cases carry three virulence factors: enterococcal surface protein ( esp ), hyaluronidase ( hyl ) and collagen-binding adhesin ( acm ) [ 83 ]. From these, only the gene acm was identified in our isolate.…”
Section: Resultsmentioning
confidence: 99%
“…They commonly cause infections of the urinary tract and wounds in hospitals, as well as endocarditis or bacteremia [5]. Most human enterococcal infections are caused by Enterococcus faecalis, accounting for 80-90% of cases, and E. faecium for most of the remaining cases.…”
Section: Introductionmentioning
confidence: 99%